System dynamics analysis of the biodiesel and CPO productions in Malaysia - Mohammadi, Sahra; Mohamed Arshad, Fatimah; Gafurjanovich, Abdulla Ibragimov (Faculty of Economics and Administration, University of Malaya, 2015)
This paper examines the biodiesel and crude palm oil productions in Malaysia using a system dynamics approach. There is an increasing demand for biodiesel in the world. The Biofuels Directive has set targets rising biodiesel production from 2% in 2005 to 20% by 2020 with Malaysia and Indonesia having the potential to capture 20% share of the biofuels market in Europe. The Malaysian government also expects that the blend 10 program of biodiesel will significantly increase demand for the feedstock including crude palm oil. This paper utilizes system dynamics approach as it enables one to capture the feedback relationships, non- linearity, and delay exist in commodity markets including palm oil. The model is simulated for 44 years starting from 1982 to 2025. The simulation results indicate that the CPO demand for biodiesel will increase in double which requires better concerns in production and stock of palm oil.